Pruning dates and productivity of cassava - Aguiar, Eduardo Barreto; Bicudo, Silvio José; Curcelli, Felipe; Figueiredo, Priscila Gonzales; Cruz, Simério Carlos Silva (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to assess different pruning dates on the development, production and quality of cassava roots. Two experiments were carried out in two regions of the state of São Paulo, Brazil: Botucatu, on clay soil, and São Manuel, on sandy soil. The experiments were carried out from September 2008 to June 2010, and harvest was done after two growing seasons (22 months). The experimental design was a randomized block design, with four replicates. Ten treatments, nine monthly pruning dates, between April and December, and a control cultivated without pruning were evaluated. Pruning dates were statistically analyzed by orthogonal contrasts, in comparison to the control, and by regression. Cassava pruning during the rest period does not alter dry matter content and root yield. However, when performed at the end of the first cycle or after the start of the second cycle, pruning reduces dry matter content and root yield.